MEDIEVAL THEATER AS MEDIUM: A SURVEY IN MEDIA ARCHAEOLOGY - Estelle Doudet (Studia Litterarum)
Media Archaeology is an emerging methodology that analyses media as modes of communication shaped by scientific innovations, cultural and social values, and imaginary representations. It also questions evolutions and ruptures in Media Cultures from Modernity and possibly before. This paper aims to demonstrate that this method offers a new approach to Production/Reception Theories in History of Literature, and an innovative way to define Medieval ‘Mediality’, with possible connections to our most recent practices. French allegorical drama offers a case study for an Archaeology of Seeing in the 15 th –16 th centuries. The article first analyses how morality plays sought to influence the public’s opinion in connecting optical science and technics with moral and religious education. Enhancing the visual possibilities of theatrical performances, Medieval allegorical drama emphathized that the medium was the message. It then investigates the public’s various responses to the plays to grasp how they operated and how efficient they really were.